1974
DOI: 10.1161/01.res.34.4.491
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin B 2 -Induced Cutaneous Vasoconstriction of the Canine Hind Paw

Abstract: The cutaneous vascular effects of prostaglandin B 2 (PGB2) were studied in dogs during constant-flow perfusion of the hind paw. The effects of PGB 2 (50-800 ng/kg min" 1 , ia) on systemic pressure, hind-paw perfusion pressure, and responses to local heating at 45°C (30 seconds) and cooling at 4°C (90 seconds) were measured in 44 dogs. PGB 2 increased perfusion pressure by 50 ± 19 mm Hg to 218 ± 21 mm Hg without any effect on systemic arterial blood pressure. The pressor response to cooling increased from 34 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This procedure also reduces the pressor response to prostaglandin B, (28) and prostaglandin F,, (29). The constrictor response to these agents is dependent on tonic sympathetic impulse activity to the canine paw.…”
mentioning
confidence: 99%
“…This procedure also reduces the pressor response to prostaglandin B, (28) and prostaglandin F,, (29). The constrictor response to these agents is dependent on tonic sympathetic impulse activity to the canine paw.…”
mentioning
confidence: 99%
“…Rightmost bar is the response to a decrease in temperature after the drug had been flushed from the bath (C2), expressed as a percentage of C1. Bars show mean ± SEM production of prostaglandins [5]. The contraction to cooling of the dartos muscle with skin was not inhibited by the cyclooxygenase inhibitor, indomethacin, and so we conclude that the mediator is not prostaglandin or any other product of the cyclooxygenase cascade.…”
Section: Discussionmentioning
confidence: 69%
“…Recent reports from our laboratory demonstrated that prostaglandin B2 (PGB2) enhanced the constrictor response of the perfused canine paw to both sympathetic nerve stimulation and local cooling while antagonizing the vasodilator response to local heating (1,2). These effects were manifested at concentrations of PGB2 that profoundly constricted the canine paw.…”
mentioning
confidence: 99%
“…It was suggested that the ability of PGB2 to enhance thermal and neurogenic vasoconstriction resulted from a selective ability of PGB compounds to facilitate catecholamine release. However, the possibility that these effects of PGB, were secondary to the increased wall stress resulting from the higher distending pressure could not be entirely eliminated (1)(2)(3).…”
mentioning
confidence: 99%
See 1 more Smart Citation